Newfoundland Loggers Respond To The Great Depression - Sutherland, Dufferin (Labour / Le Travail, 1992)
Accounts of the 1959 International Woodworkers of America strike in Newfoundland have portrayed the Newfoundland Lumbermen's Association, the local union which held jurisdiction over many of the island's loggers, as a "company union" and its president, Joseph Thompson, as a co-opted unionist. This essay examines the NLA'S origins during the 1930s and shows that Thompson built an autonomous union to improve logger's lives. The paper also brings to the fore the loggers' own experience of the Great Depression to show they did not passively accept economic hardship and exploitation and took an active role in the making of their union. At times, the loggers' militancy dictated the NLA's bargaining positions and prompted some social change in the woods. The paper concludes that while Thompson and the NLA did not view class and class conflict in explicitly political terms, it does not diminish their importance in the loggers' working lives during the 1930s.
Keywords: EXPLOITATION of humans; INTERNATIONAL Woodworkers of America (Organization); Jurisdiction; LOGGERS -- Labor unions; NEWFOUNDLAND & Labrador; STRIKES & lockouts; THOMPSON, Joseph